New 2,2-diphenylpropane and ethoxylated aromatic monoterpenes from Lavandula gibsoni (Lamiaceae) - Kulkarni, Roshan R.; Joshi, Swati P. (Natural Product Research, 2013)
A new substituted 2,2-diphenylpropane (1) and two new ethoxylated aromatic monoterpene alcohols (2 and 4) have been isolated from the acetone extract of the aerial parts of Lavandula gibsoni, along with the known compounds 8-hydroxycarvacrol (3), 8-hydroxythymol (5), coumarin (6), 4-methylresorcinol (7), 7,4-dimethylapigenin (8), salvigenin (9), -sitosteryl-3-O–D-glucopyranosyl-6-O-palmitate (10) and euscaphic acid D (11). The structures of the isolated compounds were assigned on the basis of their H-1- and C-13-NMR spectra and two-dimensional NMR techniques, which included COSY, HSQC, HMBC and NOESY experiments and comparison with the reported literature.
Keywords: 2; 2-diphenylpropane; aromatic monoterpene alcohols; Lamiaceae; Lavandula gibsoni